Nanomedicine for prion disease treatment: New insights into the role of dendrimers - McCarthy, James M. (Landes Bioscience, 2013)
Despite their devastating impact, no effective therapeutic yet exists for prion diseases at the symptomatic stage in humans or animals. Progress is hampered by the difficulty in identifying compounds that affect PrP(Sc) and the necessity of any potential therapeutic to gain access to the CNS. Synthetic polymers known as dendrimers are a particularly promising candidate in this area. Studies with cell culture models of prion disease and prion infected brain homogenate have demonstrated that numerous species of dendrimers eliminate PrP(Sc) in a dose and time dependent fashion and specific glycodendrimers are capable of crossing the CNS. However, despite their potential a number of important questions remained unanswered such as what makes an effective dendrimer and how dendrimers eliminate prions intracellularly. In a number of recent studies we have tackled these questions and revealed for the first time that a specific dendrimer can inhibit the intracellular conversion of PrP(C) to PrP(Sc) and that a high density of surface reactive groups is a necessity for dendrimers in vitro anti-prion activity. Understanding how a therapeutic works is a vital component in maximising its activity and these studies therefore represent a significant development in the race to find effective treatments for prion diseases.